SISTEM PENUNJANG KEPUTUSAN KENAIKAN JABATAN KARYAWAN PADA PT.AYN DENGAN MENERAPKAN BAHASA PEMROGRAMAN JAVA - Harahap, Ahir Yugo Nugroho (Jurnal Sistem Informasi Kaputama (JSIK), 2020)
Decision Support Systems (SPK) are designed to support all stages of decision making starting from identifying problems, selecting relevant data, determining the approach used in the decision making process, to evaluating alternative choice